2021
DOI: 10.1038/s41598-021-97323-2
|View full text |Cite
|
Sign up to set email alerts
|

Impact of cognitive reserve on dance intervention-induced changes in brain plasticity

Abstract: Dance is a complex sensorimotor activity with positive effects on physical fitness, cognition, and brain plasticity in the aging population. We explored whether individual levels of cognitive reserve (CR) proxied by education moderate dance intervention (DI)-induced plasticity assessed by resting-state functional connectivity (rs-FC) changes of the sensorimotor network (SMN), and between the dorsal attention network (DAN) and anterior default mode network (aDMN). Our cohort consisted of 99 subjects, randomly a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…They seem closely associated with proxies of the cognitive reserve such as higher education, occupational attainment or intelligence quotient (IQ) etc. (Cabeza et al, 2018;Franzmeier et al, 2017Franzmeier et al, , 2018Mitterová et al, 2021;Shalev et al, 2020). Here, we found a progressive loss of hub functional connectivity assessed by MEG in DMN, somatomotor and frontoparietal networks as well as in dorsal and ventral attention over 2 years in pwMS.…”
Section: Ta B L Ementioning
confidence: 52%
“…They seem closely associated with proxies of the cognitive reserve such as higher education, occupational attainment or intelligence quotient (IQ) etc. (Cabeza et al, 2018;Franzmeier et al, 2017Franzmeier et al, , 2018Mitterová et al, 2021;Shalev et al, 2020). Here, we found a progressive loss of hub functional connectivity assessed by MEG in DMN, somatomotor and frontoparietal networks as well as in dorsal and ventral attention over 2 years in pwMS.…”
Section: Ta B L Ementioning
confidence: 52%
“…94 Given that weekly dance practice has been shown to lead to structural brain improvements and cognitive health beyond the effects of exercise alone, 95 it is plausible to think that music and exercise in conjunction (such as dance) could represent a more robust approach to building cognitive reserve. 94,96 Further, Mitterová et al 97 suggested that there was a robust link between CR and dance-related brain plasticity. The authors longitudinally examined dance-induced neuroplastic changes in older adults, suggesting that brain plasticity was moderated by CR capacity (proxied by education).…”
Section: Mechanisms Related To Music Engagement In Dementia Preventionmentioning
confidence: 99%
“…This finding suggests that high CR individuals may have a higher capacity for plasticity at an older age, which may lead to better interventional outcomes. 97 …”
Section: Mechanisms Related To Music Engagement In Dementia Preventionmentioning
confidence: 99%
“…Several environmental changes induce neuroplasticity such as learning [ 3 , 4 ], sleep [ 5 ], aging [ 6 ], external stimuli which are accessible to sensory perception [ 7 ], and even changes in lifestyle [ 8 ]. In addition, a broad range of therapies, ranging from non-pharmacological behavioral therapies [ 9 , 10 ] to pharmacological therapies, induce electrophysiological and neuroplastic changes in the nervous system [ 11 , 12 ]. There is increasing evidence that brain stimulation techniques are beneficial in treating diseases of the brain.…”
Section: Introductionmentioning
confidence: 99%